SHELL AND TUBE TYPE HEAT EXCHANGER DESIGN TO UTILIZE EXHAUST GASES FROM THE GENERATOR - yani, indri; Hanifi, Rizal; Santosa, Aa (Universitas Majalengka, 2024)
Heat exchangers or often called heat exchangers (HE) are widely used in industry. There are many types of heat exchangers, there are fire pipes or water pipes with cross flow or unidirectional flow. Utilizing exhaust gas is an alternative to reduce costs and increase effectiveness so that wasted energy can be utilized as optimally as possible. A generator is one that can produce electrical energy which produces flue gases with a high temperature so that it can be utilized using a heat exchanger. A shell and tube heat exchanger with a fire tube type was designed. The number of pipes designed was 131 with a pipe diameter of 2.5 inches. The design results obtained from heating water are steam with a capacity of 1 ton. The dimensions of the heat exchanger are 3 meters long with a diameter of 2 meters. The heat energy produced by steam is 2852.2605KW, with a steam temperature produced of 2000C. The resulting LMTD is 360.50K. With this heat exchanger, it is hoped that the costs for producing bias steam will be as minimal as possible